Tingkat Kemampuan Berpikir Kreatif Siswa SMP dalam Menyelesaikan Mathematical Modelling Problem Ditinjau dari Self Efficacy - Antika, Helen Novi; Rahaju, Endah Budi (Universitas Negeri Surabaya, 2024)
A person's creative thinking ability is graded and can be improved by understanding creative thinking ability and its factors such as self efficacy. The purpose of this study is to describe the level of creative thinking ability of ninth grade students with high, medium, and low self efficacy in solving mathematical modelling problems. This research uses a qualitative approach with descriptive research type. For the research subject, the researcher chose three ninth grade students at Junior High School 4 Pare with different levels of self efficacy (high, medium, low), high mathematical ability, and the same gender. The researcher used self efficacy questionnaire, mathematical ability test, mathematical modeling problem, and interview to collect data. Data in the form of test results were analyzed based on Siswono's level of creative thinking ability and follow-up interviews. The results showed that in the fluency aspect, high self efficacy students could give three correct answers, moderate self efficacy students could give two correct answers, and low self efficacy students only gave one correct answer. The flexibility aspect, the three subjects can provide solutions using different ways. The novelty aspect, high self efficacy students can provide two new solutions while moderate self efficacy students and low self efficacy students produce common solutions. Based on this, high self efficacy students belong to creative thinking ability level 4 (very creative), moderate self efficacy students belong to creative thinking ability level 3 (creative), and low self efficacy students belong to creative thinking ability level 2 (quite creative).